What are institutional boundaries and how can they be overcome? Germany's collaborative research centres as boundary-spanning networks - Grit Laudel; Jochen Gläser (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Social entities create institutional frameworks, i.e. internal systems of rules which govern (but do not control) the actions of their members. Both scientific communities and scientific organisations are social entities whose institutional frameworks include rules promoting internal collaboration. Based upon a diffuse reciprocity, members of the social entities are stimulated to collaborate with other members. The tendency to prefer other members as collaborators is accompanied by a relative exclusion of non-members from collaborations. Thus, in this way institutional frameworks create institutional boundaries hindering collaboration. In order to overcome institutional boundaries both within universities and between scientific communities, in Germany collaborative research centres (CRCs) were established. These are networks of research groups from different departments of one or more universities, i.e. from different organisations and different scientific communities. They contain their own institutional framework, which overlaps with the institutional frameworks of both organisations and scientific communities. Because the network's institutional framework includes rules promoting collaborations, these necessarily span the original institutional boundaries. A detailed discussion of these rules shows the functional equivalence of the different social entities' (communities, organisations and networks) institutional frameworks. – – Scientific communities und formale Organisationen wie Forschungsinsitute oder Universitäten bilden jeweils eigene Institutionensysteme aus. Diese Institutionensysteme fördern direkt oder vermittelt Kooperationen zwischen den Mitgliedern der communities bzw. Organisationen. Indem sie Kooperationen zwischen ihren Mitgliedern fördern, errichten sie aber zugleich institutionelle Schranken für die Kooperation mit Außenstehenden. Solche Kooperationen werden durch die Institutionensysteme meist nicht unterstützt und damit relativ erschwert. Die Mitglieder einer scientific community oder Organisation wählen deshalb tendenziell Kooperationspartner aus derselben community bzw. Organisation. Um solche institutionellen Schranken zu überwinden, hat die Deutsche Forschungsgemeinschaft das Förderprogramm `Sonderforschungsbereiche' (SFB) etabliert. Dabei handelt es sich um Netzwerke von Forschungsgruppen, die aus verschiedenen Fachbereichen einer oder mehrerer Universitäten stammen. Die Sonderforschungsbereiche bilden ein eigenes Institutionensystem aus, das die der scientific communities und der Organisationen überlagert. Weil auch dieses Institutionensystem kooperationsfördernde Regeln enthält, werden innerhalb eines SFB solche Kooperationen gefördert, die die klassischen institutionellen Grenzen überschreiten. Eine Analyse der kooperationsfördernden Regeln von SFB zeigt, daß sie den in scientific communities und Organisationen entstehenden Regeln funktional äquivalent sind.
Keywords: 300; Forschungskooperation; Forschungs- und Technologiepolitik; Deutschland